IMPLIKATUR DALAM NOVEL TUHAN, IZINKAN AKU MENJADI PELACUR! KARYA MUHIDIN M. DAHLAN - Asriani, Asriani (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
This study examines maxim violations and implicatures in novel Tuhan, Izinkan Aku menjadi Pelacur! by Muhidin M. Dahlan. This research aims: (1) to describe the violations of the maxims contained in novel Tuhan, Izinkan Aku menjadi Pelacur! by Muhidin M. Dahlan and (2) describe the types of implicature contained in novel Tuhan, Izinkan Aku menjadi Pelacur! by Muhidin M. Dahlan. In order to answer the existing problem formulation, this study uses the cooperative theory proposed by Yule (2014) to answer the first problem formulation that addresses the maxim violation. Then, to answer the second problem formulation that discusses the types of implicature using Grice's theory of conversational implicature. This research is included in the type of library research using a qualitative descriptive approach. The data and data sources used in this study are sentences in the form of dialogue contained in novel Tuhan, Izinkan Aku menjadi Pelacur! by Muhidin M. Dahlan. Then, the data collection technique used is the technique of reading and recording using four stages in the analysis, namely: the identification stage, the classification stage, the interpretation stage and the conclusion drawing stage. The results of the study: (1) there are four maxims violations in novel Tuhan, Izinkan Aku menjadi Pelacur! Muhidin M. Dahlan's work, namely: violating the quality maxim, violating the quantity maxim, violating the behavior maxim, and violating the relation maxim. (2) There are four types of implicature in novel Tuhan, Izinkan Aku menjadi Pelacur! by Muhidin M. Dahlan's works, namely: general conversation implications, scale conversation implications, special conversation implications, and conventional conversation implications.